KAJIAN TATA RUANG UNTUK MENERAPKAN SISTEM INSENTIF PEMANFAATAN RUANG PADA PROYEK KPS (KERJA SAMA PEMERINTAH SWASTA) JALAN TOL (STUDY KASUS KAKI NUSA DUA PADA JALAN TOL BALI MANDARA) - Putu Ika Wahyuni; Sarwono Hardjomuljadi; Hendrik Sulistio; K. Koespiadi (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
ABSTRACT The Government of Indonesia was committed to encouraging public-private partnership (PPP) schemes to address gaps in infrastructure development. But not all projects offered through the PPP scheme have a high degree of eligibility because the project is a long-term investment with a considerable degree of risk challenge. Efforts to improve the feasibility of investing in toll road PPP projects were made such as investment guarantees and incentives for the private sector. This study is a continuation of previous research that was an implementation of the incentive system in PPP project contract to increase investment feasibility. In this study, the authors want to obtain a general description of:(1) Existing condition of research location and land use based on Local Regulation around Bali Mandara Highway (Field Observation and Local Regulation), (2) To know the wishes of the people around Highway in a location that allows applied spatial use incentive system (Interview Method), (3) Assessing the spatial plan at the foot of the toll road regarding spatial use plan with guidance on incentives and density utilization of space on the highway (method of cropping the map). From the result of the research, it can be seen the general description of the people's desire to play a role in the utilization of space around the Nusa Dua toll, where the results of satellite image analysis and the spatial regulation on spatial planning allow the availability of land for spatial use activities around highway about 10 hectares. Keywords: highway, KPS, spatial, use of space